International business: Raising cultural awareness in global negotiating - Gardašević, Jovana; Vapa-Tankosić, Jelena (The European Journal of Applied Economics, 2015)
The global marketplace is a fast-growing and rapidly changing field. Global negotiation is a process where each party from two or more different countries involved in negotiating tries to gain an advantage for itself by the end of the process. The process of global negotiating differs from culture to culture in terms of language, different types of communication (verbal and nonverbal), negotiating style, approaches to problem – solving, etc. The aspects of culture that are of vital importance for global negotiating are attitudes and beliefs, religion, material culture, and language. This paper should encourage better understanding of the process of negotiation: it defines the negotiation process, identifies the issues that are subject to negotiation and mentions the stages of negotiation. It discusses the importance of developing cultural awareness prior to negotiating internationally through descriptive overview of all aspects of culture. It gives examples of differences in global negotiating and doing business worldwide. The purpose of this paper is to show theoretically the connection between these terms and provide information that will prevent business people from making mistakes and pitfalls in international negotiation process.